Cross-market spillovers amid policy uncertainty era of China’s economy - Yun Song; Kai-Hua Wang; Hong-Wen Liu; Nicoleta-Claudia Moldovan (PLoS ONE, 2026)
This study meticulously discusses spillover effects among agricultural futures (AGF), crude oil prices (CRO), and the U.S. dollar (USD) during the volatile phase of China’s economic policy (CEPU), utilizing the quantile connectedness approach. The empirical findings show that, in the face of economic instabilities and tail incidents, AGF, CRO, USD, and CEPU exhibit significantly higher return spillover at extreme quantiles in comparison to mean one. Furthermore, the dynamic properties of AGF, CRO, USD, and CEPU are empirically substantiated, and certain crises obviously enhance these spillover effects. The primary innovation involves the integration of CEPU into the analytical framework of the agriculture-energy-financial system. This integration illustrates the interdependencies of the system across a variety of market conditions through dynamic quantile shifts, thereby expanding the theoretical scope. This study recommends actions for different market participants, such as an cross-nation economic cooperation and financial market tracking mechanism.